Odpowiedzi

2010-04-11T14:17:16+02:00
D) 2(x+y)-2=3(x+2)
2(y+2)+3(x-y)=2x-1

2x+2y-2=3x+6
2y+4+3x-3y=2x-1

2x+2y-3x=6+2
-y+3x-2x=-1-4

-x+2y=8
x=-5+y

-(-5+y)+2y=8
x=-5+y

5-y+2y=8
x=-5+y

y=8-5
x=-5+y

y=3
x=-5+3

y=3
x=-2

e)9x+8y=1 |×1,5
5x-6y=11 |×2

13,5x+12y=1,5
10x-12y=22
+_____________
23,5x=23,5 |:23,5
x=1

9×1+8y=1
8y=1-9
8y=-8 |:8
y=-1

f)x+7y=22
y=5x-2

x+7×(5x-2)=22
y=5x-2

x+35x-14=22
y=5x-2

36x=22+14
y=5x-2

36x=36 |:36
y=5x-2

x=1
y=5×1-2

x=1
y=5-2

x=1
y=3

g)y=2x-8
-12x+9y= -6

y=2x-8
-12x+9×(2x-8)=-6

y=2x-8
-12x+18x-72=-6

y=2x-8
6x=-6+72

y=2x-8
6x=66 |:6

y=2x-8
x=11

y=2×11-8
x=11

y=22-8
x=11

y=14
x=11


Polecam się na przyszłość w razie pytań pisać na gg 5891597 pozdrawiam Tutti123 :)